2016
DOI: 10.1515/hf-2016-0213
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effect of NP fire retardant pre-treatment on heat-treated poplar wood. Part 2: hygroscopicity, leaching resistance, and thermal stability

Abstract: In continuation of the previous study concerning the effects of a combined treatment of wood with nitrogen-phosphorus (NP) fire retardant and heat treatment (HT), the hygroscopicity, leachability, thermal stability, Fourier transform-infrared (FT-IR) spectra, and X-ray diffraction (XRD) properties of Populus beijingensis W.Y. Hsu have been investigated. The wood samples were impregnated with 10% NP fire retardant solution and exposed to HTs at 140°C–160°C for 30 min. HT of NP treated wood reduced the moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The reason is that the HT increased the hydrophobicity and the TM process further enhanced the surface density of WHT-TM. The compression stability of WHT-TM samples remarkably enhanced due to the NP pre-treatment and the acceleration effect of NP on wood thermal degradation during the thermo-densification process [29,33]. When compared with that of WTM, the HDfs value was 31.60% higher and the Tr value decreased from 26.65% to 6.07%.…”
Section: Compression Recovery Of the Functionalized Surface Layer Durmentioning
confidence: 98%
See 2 more Smart Citations
“…The reason is that the HT increased the hydrophobicity and the TM process further enhanced the surface density of WHT-TM. The compression stability of WHT-TM samples remarkably enhanced due to the NP pre-treatment and the acceleration effect of NP on wood thermal degradation during the thermo-densification process [29,33]. When compared with that of WTM, the HDfs value was 31.60% higher and the Tr value decreased from 26.65% to 6.07%.…”
Section: Compression Recovery Of the Functionalized Surface Layer Durmentioning
confidence: 98%
“…Then, they were divided into six groups (Table 1), each comprised of 15 samples. The NP impregnation and HT conduction protocols were kept the same as in former studies [29,33]. Samples in groups W NP-TM , W TM , and W HT-TM were pre-heated using a thermo-compressor (MLG68-S, Zhengzhou, China) for 5 min, then thermo-mechanically pressed to 14 mm final thickness using a stopper for 20 min at constant temperature.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad peak that occurs at 3400-3200 cm −1 was associated with -OH stretching in hydroxyl groups originating mainly from cellulose [36]. The absorption at 1740 cm −1 was due to C=O stretching of xylan [37]. The peak at 1034 cm −1 was attributed to C-O-C stretching of aliphatic ether bond [4].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Our research group attempted to enhance the leachability and hygroscopicity of NP, as well as smoke development during burning [16]. Recent studies revealed that NP also has an intensification effect on high-temperature (HT) treatment of wood [17,18]. In Part 1 of this study, it was reported that the combined process of using NP fire retardant and TM methods improved compression recovery and combustion safety.…”
Section: Introductionmentioning
confidence: 96%